Treatment patterns among colorectal cancer patients in South Australia: a demonstration of the utility of population‐based data linkage. Issue 4 (22nd May 2014) - Beckmann, Kerri R.; Bennett, Alice; Young, Graeme P.; Roder, David M.
Abstract Rationale, aims and objectives Population level data on colorectal cancer (CRC) management in Australia are lacking. This study assessed broad level patterns of care and concordance with guidelines for CRC management at the population level using linked administrative data from both the private and public health sectors across South Australia. Disparities in CRC treatment were also explored. Method Linking information from the South Australian Cancer Registry, hospital separations, radiotherapy services and hospital‐based cancer registry systems provided data on the socio‐demographic, clinical and treatment characteristics for 4641 CRC patients, aged 50–79 years, diagnosed from 2003 to 2008. Factors associated with receiving site/stage‐specific treatments (surgery, chemotherapy and radiotherapy) and overall concordance with treatment guidelines were identified using Poisson regression analysis. Results About 83% of colon and 56% of rectal cancer patients received recommended treatment. Provision of neo‐adjuvant/adjuvant therapies may be less than optimal. Radiotherapy was less likely among older patients (prevalence ratio 0.7, 95% confidence interval 0.5–0.8). Chemotherapy was less likely among older patients (0.7, 0.6–0.8), those with severe or multiple co‐morbidities (0.8, 0.7–0.9), and those from rural areas (0.9, 0.8–1.0). Overall discordance with treatment guidelines was more likely among rectal cancer patients (3.0, 2.7–3.3), older patients (1.6, 1.4–1.8), those with multiple co‐morbid conditions (1.3, 1.1–1.4), and those living in rural areas (1.2, 1.0–1.3). Conclusions Greater emphasis should be given to ensure CRC patients who may benefit from neo‐adjuvant/adjuvant therapies have access to these treatments.